The influence of the ovarian-menstrual cycle phases on the psychological functioning of female athletes - Shan, M.; Kozhedub, M.S.; Vrublevskiy, E.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the dynamics of subjective assessment of the psychofunctional state of female athletes of various specialisations throughout the ovarian-menstrual cycle. Methods and structure of the study. The WAM questionnaire (well-being, activity, mood) was used to record changes in the psychofunctional state of the athletes examined. To determine the psychofunctional state of the athletes examined at different phases of the ovarian-menstrual cycle (OMC), the questionnaire test for differential self-assessment of the functional state WAM (well-being, activity, mood), which allows for a rapid assessment of a person’s condition during periods of mental and physical stress [2]. An assessment of situational (reactive) anxiety [5] was also carried out as a condition characterised by subjectively experienced emotions: tension, restlessness, concern, nervousness, etc. The experiment involved female athletes aged 15-17 who specialise in sprinting and ice hockey. Results and conclusions. The article presents the dynamics of subjective assessment of the psychofunctional state throughout the ovarian-menstrual cycle (OMC) in female athletes. It is shown that the psychofunctional state of female athletes changes in accordance with the phases of their individual specific biological cycle, and taking this into account when designing a training programme can increase its effectiveness without excessively increasing the volume and intensity of the training activities used.